Russia and Poland – a ‘domestic row’ of Slavs, or a conflict of mentalities? - Aleksander W. Lipatow (Napis, 2022)
The article presents a cross-section sketch of the attitude of Russia toward Poland and the Polish people, demonstrating its ambivalence, stretching between Polonophobia and Polonophilia (‘the complex of unrequited love toward Poland’). Its sources are generally thought to lie in the elementary mental disparity between Moscow’s total absolutism and Polish civil society, based on individualism, Latin culture and the Roman law. This disparity becomes a centuries-old source of political conflict and cultural fascination.